Effects of antioxidants on contracting spinotrapezius muscle microvascular oxygenation and blood flow in aged rats - Herspring, Kyle F. (Kansas State University, 2008)
Aged rats exhibit a decreased muscle microvascular O[subscript]2 partial pressure (PO[subcript]2mv) at rest as well as during contractions compared to young rats and this may contribute to their reduced exercise tolerance. Age-related reductions in nitric oxide (NO) bioavailability due, in part, to elevated reactive O[subscript]2 species (ROS) constrain muscle blood flow (Qm). Therefore, antioxidants may restore NO bioavailability, Qm and ameliorate the reduction in PO[subscript]2mv and hence the decrease in exercise tolerance seen in aged rats. PURPOSE: To test the hypothesis that antioxidants would elevate Qm at rest and during contractions and therefore PO[subscript]2mv in aged muscle. METHODS: PO[subscript]2mv and Qm were measured in the spinotrapezius while muscle oxygen consumption (VO[subscript]2m) was estimated in 20 anesthetized male Fisher 344 x Brown Norway hybrid (F344xBN) rats at rest and during 1 Hz contractions before and after antioxidant intravenous infusion (76mg/kg vitamin C and 52mg/kg tempol). Moreover, muscle force production was measured in a subset of animals. RESULTS: Before infusion, contractions invoked a biphasic PO[subscript]2mv that fell from 30.6 [plus or minus] 0.9 mmHg to a nadir of 16.8 [plus or minus] 1.2 mmHg with an 'undershoot' of 2.8 [plus or minus] 0.7 mmHg below the subsequent steady-state (19.7 [plus or minus] 1.2 mmHg). Antioxidants elevated baseline PO[subscript]2mv to 35.7 [plus or minus] 0.8 mmHg (P<0.05) and reduced or abolished the 'undershoot' (P<0.05) without changing the steady-state contracting PO[plus or minus]2mv. Antioxidants did not change Qm at rest but during contractions Qm was reduced from 157 [plus or minus] 28 to 91 [plus or minus] 15 ml min[superscript]-1 100g[superscript]-1 (P<0.05). Antioxidants produced no significant effect on VO[subscript]2m. However, antioxidant supplementation produced a 16.5% decrease (P<0.05) in muscle force production that occurred within the first contraction and remained throughout the duration of stimulation. In addition, the ratio of muscle force production to VO[subscript]2m (F/VO[subscript]2m) actually increased from 0.92 [plus or minus] 0.03 to 1.06 [plus or minus] 0.6 (P<0.05) following infusion of antioxidants. CONCLUSION: Antioxidant supplementation significantly alters the balance between muscle O[subscript]2 delivery and VO[subscript]2 at rest and during contractions, which modifies the microvascular PO[subscript]2mv profile. Specifically, antioxidants elevate PO[subscript]2mv, which improves the potential for diffusive blood-myocyte flux. This effect arises, in part, from the unanticipated fall in muscle force production consequent to antioxidant supplementation.
Keywords: aging; muscle microvascular oxygenation; blood flow; antioxidant supplementation; Health Sciences, Health Care Management (0769); Health Sciences, Medicine and Surgery (0564)